Absent monofilament sensation in a type 2 diabetic feet*. Issue 5 (3rd September 2017) - Cheong, Julia; Alexiadou, K.; Devendra, Senan
Abstract: Neuropathy is a common complication which can affect up to 90% of patients with diabetes mellitus. Asymptomatic neuropathy is a common presentation. We present a case that emphasises the importance of foot screening in people with diabetes. It also highlights that patient education is key to prevent development of foot ulceration which can lead to amputations. In addition, pharmacological therapy (as per NICE guidance) can be offered for pain relief. Patients with diabetic neuropathy are at high risk of falling and sustaining fractures.